MANAJEMEN STRATEGI DALAM MENGHADAPI PERSAINGAN BISNIS ( STUDI KASUS DEALER ASTRA HONDA MOTOR DI KOTA BENGKULU ) - Endah Anggraini Mia Susanti; Sri Ekowati ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
Strategy is a managerial process to develop and maintain harmony between company goals, company resources, and market opportunities that are constantly changing, with the aim of shaping and adapting the company's business and products, so as to achieve profits and profitable growth rates. In addition to the use of strategy, the application of ethics is very important to avoid unfair competition between business people. The objectives of this study are: to analyze the management strategy that is suitable for use at PT Astra Honda Motor in the city of Bengkulu. The technique of this research is through field research techniques, and includes qualitative descriptive research. The results of the study indicate that: strategic management analysis is suitable for use by PT Astra Honda Motor in the city of Bengkulu in order to increase the number of sales: 1) Strength (strength) of the company, namely as a dealer in Bengkulu City which has complete facilities and infrastructure in the marketing and maintenance process of Honda motorcycles; 2) Weaknesses (weaknesses) of the company, namely the lack of promotion, integration of data and information between CV. Astra Honda Motor Bengkulu City and PT. Astra Honda Motor is inadequate to obtain information quickly and accurately; 3) Opportunities (opportunities) for the company, namely a large market share; 4) Threats (threats) for the company, namely the presence of new competitors such as Bajaj and Chinese motorcycles, the community paradigm in assessing product superiority based on certain events, rapidly changing community trends so that they prefer new products that appear on the market and the level of use of motorcycles the higher it also triggers the high number of accidents that occur on the highway so that people hesitate in determining the type of vehicle to be chosen; 5) Based on the results of the SWOT analysis, the strategies that can be carried out by the company are the Market Development Strategy, Product Development Strategy, and Brand Image Strategy.Â Keywords: Analysis, Strategic Management, Business Competition